Digital Financial Literacy As an Antecedent to Financial Inclusion and MSME Performance - Normawati, Rani Arifah; Santoso, Eko Esti; Latifah , Nunuk (Universitas Muhammadiyah Sorong, 2025)
MSMEs experience various vulnerabilities that emphasize the importance of government digital onboarding programs as part of financial inclusion. To address these challenges, it is crucial to understand the role of digital financial literacy in enhancing access to financial services and improving business performance. This study investigates the influence of digital financial literacy on financial inclusion and MSME performance, with a focus on digital finance adoption and access as key of financial inclusion. Employing a quantitative research approach, the study surveyed 400 MSMEs in East Java, Indonesia, using a structured questionnaire and purposive sampling technique. Descriptive statistical analysis was conducted to outline the characteristics of the data. To explore the relationships among the variables, Partial Least Squares Structural Equation Modeling (PLS-SEM) was utilized with WarpPLS software. The analysis reveals that digital financial literacy significantly impacts digital finance adoption, which, in turn, enhances MSME performance. However, access to digital finance, while positively associated with digital finance adoption, does not show a significant direct impact on MSME performance. The results highlight the need for targeted educational programs to boost digital financial literacy among MSMEs, ensuring that digital financial tools are effectively utilized to foster business growth and financial inclusion.